Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1939-8433-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing down the targets for yield improvement in rice under normal and abiotic stress conditions via expression profiling of yield-related genes

Abstract: BackgroundCrop improvement targeting high yield and tolerance to environmental stresses has become the need of the hour. Yield improvement via breeding or gene pyramiding aiming comprehensive incorporation of the agronomically favored traits requires an in-depth understanding of the molecular basis of these traits. The present study describes expression profiling of yield-related genes in rice with respect to different developmental stages and various abiotic stress conditions.ResultsOur analysis indicates dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…Amongst these, transcriptional regulation is a major means to regulate the cellular levels and hence the activity of an encoded protein. Consistently, gene expression-based studies in plants have shown that transcript profiles of genes usually correlate well with their role in physiology and development [29,40]. Hence, studying the transcript profiles of genes which do not have well described role during the course of a plant’s life cycle, may provide meaningful insights into their function.…”
Section: Discussionmentioning
confidence: 93%
“…Amongst these, transcriptional regulation is a major means to regulate the cellular levels and hence the activity of an encoded protein. Consistently, gene expression-based studies in plants have shown that transcript profiles of genes usually correlate well with their role in physiology and development [29,40]. Hence, studying the transcript profiles of genes which do not have well described role during the course of a plant’s life cycle, may provide meaningful insights into their function.…”
Section: Discussionmentioning
confidence: 93%
“…The gene expression at various developmental stages and tissues of rice was analysed using publicly available data from the microarray platform-51K Affymetrix chips on Genevestigator (https://www.genevestigator. com; Hruz et al 2008;Tripathi et al 2012).…”
Section: Functional Classification and Gene Meta-analysismentioning
confidence: 99%
“…IPT, the key enzyme in the process of CTK synthesis, is involved in adaption to heat, drought, osmotic stress, and salt stress in maize, peanut, and Arabidopsis (Vyroubalová et al, 2009; Qin et al, 2011; Skalák et al, 2016). In rice, LOG expression is altered by various abiotic stress conditions, including heat stress, cold stress, drought, and salinity (Tripathi et al, 2012). CYP735A expression in rice was altered by exposure to cold and dehydration (Maruyama et al, 2014).…”
Section: Introductionmentioning
confidence: 99%